A technical modification of video‐assisted ablation for recurrent pilonidal sinus. (November 2014) - Milone, M.; Bianco, P.; Musella, M.; Milone, F.
Abstract Aim The study evaluated, in a proof of concept, the usefulness of a prosthesis (plug) in addition to video assisted ablation of pilonidal sinus (VAAPS) for treatment of recurrent pilonidal sinus. Method This is a case series of recurrent complex pilonidal sinus treated by VAAPS plus plug positioning. Results Four patients were analysed. All were successfully treated by this new approach. No difficulties in inserting the plug were identified. Complete healing was achieved in all cases. No infection or recurrence was reported during a limited follow‐up. Conclusion This new technique allows a minimally invasive scarless approach to recurrent pilonidal sinus.